2019
DOI: 10.1109/access.2019.2909408
|View full text |Cite
|
Sign up to set email alerts
|

Increasing LPWAN Scalability by Means of Concurrent Multiband IoT Technologies: An Industry 4.0 Use Case

Abstract: One of the most important challenges of the Internet of Things (IoT) in the next years will be the smooth incorporation of millions of smart devices into its communications paradigm. The greater coverage area of sub-1-GHz low-power wide area networks (LPWANs) makes them a suitable technology to easily encompass hundreds of end devices under a single base station. However, LPWAN inherent simplicity affects negatively on scalability, as these networks are not flexible enough to deal with a high number of nodes u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 27 publications
0
18
0
2
Order By: Relevance
“…Scalability and multihop optimization: The scalability of single-hop LoRaWAN has been extensively studied, and it is one of the main challenges of the technology. When the traffic load or the node density increases, the network performance can be severely affected [ 12 , 13 , 15 ]. Some works propose to improve scalability at the MAC layer level of LPWAN, using techniques such as scheduled MAC protocols, station grouping algorithms, adaptive transmission mode, and adaptive power control [ 14 , 58 ], or even using concurrent multiband technologies [ 15 ].…”
Section: Open Issues and Future Directionsmentioning
confidence: 99%
See 4 more Smart Citations
“…Scalability and multihop optimization: The scalability of single-hop LoRaWAN has been extensively studied, and it is one of the main challenges of the technology. When the traffic load or the node density increases, the network performance can be severely affected [ 12 , 13 , 15 ]. Some works propose to improve scalability at the MAC layer level of LPWAN, using techniques such as scheduled MAC protocols, station grouping algorithms, adaptive transmission mode, and adaptive power control [ 14 , 58 ], or even using concurrent multiband technologies [ 15 ].…”
Section: Open Issues and Future Directionsmentioning
confidence: 99%
“…Several works have shown that dense networks with many devices may degrade the overall network performance with longer delays and low reliability [12][13][14]. LoRaWAN uses ALOHA as the Medium Access Control (MAC) protocol, which does not perform well when traffic load or node density increases, due to interference and packet collisions [15,16]. Multihop strategies may also contribute to improve scalability, capacity, and reliability, as pointed in [12,15].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations